2019
DOI: 10.5194/amt-12-1029-2019
|View full text |Cite
|
Sign up to set email alerts
|

An improved total and tropospheric NO<sub>2</sub> column retrieval for GOME-2

Abstract: Abstract. An improved algorithm for the retrieval of total and tropospheric nitrogen dioxide (NO2) columns from the Global Ozone Monitoring Experiment-2 (GOME-2) is presented. The refined retrieval will be implemented in a future version of the GOME Data Processor (GDP) as used by the EUMETSAT Satellite Application Facility on Atmospheric Composition and UV Radiation (AC-SAF). The first main improvement is the application of an extended 425–497 nm wavelength fitting window in the differential optical absorptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 97 publications
4
52
0
Order By: Relevance
“…Previous GOME-2 validation highlighted the effect of GOME-2 large pixels, and the aerosol shielding effect, leading e.g., to differences of 5% to 25% over China (Ma et al, 2013;Wu et al, 2013;Drosoglou et al, 2018). Liu et al (2019b) showed possible improvements of the GDP 4.8 product, leading to reduced discrepancies of the satellite-to-ground-10 based biases of the order of 10% to 25% for several MAX-DOAS stations.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…Previous GOME-2 validation highlighted the effect of GOME-2 large pixels, and the aerosol shielding effect, leading e.g., to differences of 5% to 25% over China (Ma et al, 2013;Wu et al, 2013;Drosoglou et al, 2018). Liu et al (2019b) showed possible improvements of the GDP 4.8 product, leading to reduced discrepancies of the satellite-to-ground-10 based biases of the order of 10% to 25% for several MAX-DOAS stations.…”
mentioning
confidence: 98%
“…JAMSTEC data from the MADRAS network have been used in Kanaya et al (2014) for the validation of the OMI DOMINO and NASA 30 tropospheric NO2 data. BIRA-IASB MAX-DOAS stations have been regularly used for the validation of GOME-2 GDP products from MetOp-A and MetOp-B (Valks et al, 2011;Pinardi et al, 2011;Liu et al, 2019b) as part of the AC SAF activities (Hassinnen et al, 2016; see also www.cdop.aeronomie.be/validation/validresults). Pandora datasets have also been used in satellite validation of total and tropospheric NO2 columns (Herman et al 2009;Tzortziou et al, 2014;Judd et al, 2019) and a recent study of Herman et al (2019) 35 presented an overview at 14 Pandora sites showing that NASA OMI NO2 overpass data consistently underestimate the Pandora derived NO2 amounts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of clouds is taken into account in the NO 2 AMF calculation using cloud parameters based on the Optical Cloud Recognition Algorithm (OCRA) and the Retrieval Of Cloud Information using Neural Networks (ROCINN) algorithms (Loyola et al, 2007(Loyola et al, , 2011. OCRA/ROCINN has been applied in the operational retrieval of trace gases from GOME (Van Roozendael et al, 2006), GOME-2 (Valks et al, 2011;Hao et al, 2014;Liu et al, 2019b), and TROPOMI (Heue et al, 2016;Theys et al, 2017;Loyola, in preparation). The latest version of OCRA/ROCINN (Lutz et al, 2016;Loyola et al, 2018) provides two sets of cloud products: one treats clouds as ideal Lambertian reflectors in a "Clouds-as-Reflecting-Boundaries" (CRB) model, and the second treats clouds as uniform layers of water droplets in a "Clouds-As-Layers" (CAL) model.…”
Section: Introductionmentioning
confidence: 99%